(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the evolution of theoretical approaches to the problem of psychological stability. It highlights the content of the concept of psychological stability, its formation and its place in modern psychology. Also, the importance of psychological stability in individual activity, the processes of adaptation in stressful situations and maintaining mental balance are analyzed based on scientific sources. The article studies the components of psychological stability, its connection with the adaptation process, and the views of various scientists on this problem